Evaluation of marker gene expression as a potential predictive marker of leukopenic toxicity for inactivated influenza vaccines - Sasaki, Eita; Momose, Haruka; Hiradate, Yuki; Furuhata, Keiko; Takai, Mamiko; Kamachi, Kazunari; Asanuma, Hideki; Ishii, Ken J.; Mizukami, Takuo; Hamaguchi, Isao (Biologicals, 2017)
The leukopenic toxicity test (LTT) is used to evaluate the safety and lot-to-lot consistency of influenza hemagglutinin split vaccine (HAv) and is included in the Japanese Minimum Requirements for Biological Products. LTT assesses the reduced leukocyte levels in murine peripheral blood after HAv administration. However, they require large numbers of animals, and therefore it would be beneficial to develop a more accurate and sensitive alternative method. In this study, we selected biomarkers of leukocyte reduction from 18 previously identified marker genes that were associated with an abnormal toxicity test (ATT). Among these 18 genes, the expressions of 15 marker genes were strongly associated with leukocyte reduction levels. A stepwise single addition multiple regression analysis was used to further extract the genes responsible for leukocyte reduction, with significant (p < 0.25) regression coefficients. The expression of 7 genes significantly predicted the leukocyte reduction. The prediction accuracy of this approach was approximately >90% (mean) for the direct measurement of leukocyte numbers. These results indicate that the expression of these 18 previously identified genes can provide information for both ATT and LTT.